Analyzing the Effect of Foreign Language on Decision Making : A Study From Bangla Language Perspective (Dhaka University Journal of Biological Sciences, 2020)
Decision making is one of the crucial aspects of our daily life. In terms of making any decision language plays a vital role either directly or indirectly. The purpose of the present study was to investigate the impact of Bangla language (native) and foreign language (English) on decision making. It was hypothesized that foreign language would show fewer decision biases. Total 80 participants (40 males, 40 females) took part in this experiment. Results from Chi-square test revealed that while making decisions in Bangla language under loss-frame 68.7% participants preferred to choose risk option over sure option. On the contrary in gain-frame only 29.9% participants preferred the risk option (χ2(1, N = 80) = 24.059, p < 0.001). This decision biasness was significantly minimized in English language. In loss-frame 56.1% participants preferred the risk option over sure option and in gain-frame 43.6% participants preferred the risk option, χ2(1, N = 80) = 2.502, p > 0.05.Dhaka Univ. J. Biol. Sci. 29(2): 191-199, 2020 (July)